MEDIATION AS AN ALTERNATIVE SETTLEMENT ON OIL PALM PLANTATION DISPUTE (A Lesson from Oil Palm Plantation Mediation in Sidomulyo Village, Ogan Komering Ilir District, South Sumatera Province) - Adrian Nugraha (Jurnal Dinamika Hukum, 2017)
Mediation is considered as one of the effective solutions to resolve as well as tool to alter oil palm plantation disputes. This research was conducted with socio-legal approach. The test method was done by descriptive qualitative data analysis which describes a situation or phenomenon with words or sentences then separated by category for the conclusion. This research finding suggests that mediation has played a crucial role especially in decreasing the dispute intensity and achieving the agreement between conflicting parties. Subsequently, Mediation by integrated team of dispute resolution was divided into two stages: first stage was commencement of the mediation process and the second was implementation of mediation. Furthermore, several approaches that can do to alter dispute into a long-term harmonious relationship, namely: first, using the legal certainty approach, second, Company–community partnerships approach and third, capacity building for mediator approach.Keywords: altering dispute, mediation, oil palm plantation